2009
DOI: 10.5194/hessd-6-535-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inclusion of potential vorticity uncertainties into a hydrometeorological forecasting chain: application to a medium size basin of Mediterranean Spain

Abstract: Abstract. The improvement of the short- and mid-range numerical runoff forecasts over the flood-prone Spanish Mediterranean area is a challenging issue. This work analyses four intense precipitation events which produced floods of different magnitude over the Llobregat river basin, a medium size catchment located in Catalonia, north-eastern Spain. One of them was a devasting flash flood – known as the "Montserrat" event – which produced 5 fatalities and material losses estimated at about 65 million euros. The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…On one hand, efforts have been devoted to the assessment of the predictive ability of meteorological models with respect to severe rainfall events (Petroliagis et al, 1997;Romero et al, 2005;Hohenegger et al, 2006Hohenegger et al, , 2008Davolio et al, 2007;Schär, 2007a, 2007b;Argence et al, 2008;Lebeaupin et al, 2008;Amengual et al, 2009;Lapeyre and Talagrand, 2009): their goal is to evaluate how closely a particular model can predict the true state of a certain severe rainfall scenario as a function of observational data quality and availability, parametrization of the subgrid processes, model coupling, model approximations and resolution. On the other hand, some studies have investigated the dynamical, kinematical and microphysics properties of observed systems (Leckebusch and Ulbrich, 2004;Grazzini, 2007;Miglietta and Regano, 2008;Sanchez-Gomez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, efforts have been devoted to the assessment of the predictive ability of meteorological models with respect to severe rainfall events (Petroliagis et al, 1997;Romero et al, 2005;Hohenegger et al, 2006Hohenegger et al, , 2008Davolio et al, 2007;Schär, 2007a, 2007b;Argence et al, 2008;Lebeaupin et al, 2008;Amengual et al, 2009;Lapeyre and Talagrand, 2009): their goal is to evaluate how closely a particular model can predict the true state of a certain severe rainfall scenario as a function of observational data quality and availability, parametrization of the subgrid processes, model coupling, model approximations and resolution. On the other hand, some studies have investigated the dynamical, kinematical and microphysics properties of observed systems (Leckebusch and Ulbrich, 2004;Grazzini, 2007;Miglietta and Regano, 2008;Sanchez-Gomez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The automatic procedure uses as objective function the root mean square error weighted according to the peak; and as search algorithm, the univariate-gradient method (USACE-HEC, 2000). A complete description of the HEC-HMS set-ups and the calibration and validation tasks for both catchments can be found in (Amengual et al, 2007(Amengual et al, , 2009(Amengual et al, , 2015. …”
Section: The Hec-hms Modelmentioning
confidence: 99%
“…This fact highlights the highly nonlinear nature of the rainfall-runoff transformation in semi-arid basins. (Table 3 ; for further information about the values of the Qp T s, see Amengual et al (2009Amengual et al ( , 2015.…”
Section: Qdf Evaluationmentioning
confidence: 99%
See 2 more Smart Citations